Strategi Sekolah Tahfidz Dalam Meningkatkan Daya Saing Sekolah - Irwan Desiharto; Kun Nurachadijat (Al-Mau'izhoh, 2023)
The purpose of this study is the background of how the quantity of new students to private schools plus the Quran. This study also aims to find out: Tahfidz school strategy to increase competitiveness against PPDB and Implementation (implementation of SD Muhammad Al-'Unaizy education). In this study researchers used qualitative analytical descriptive methods with inductive data collection, research data was collected by several methods. The results of this study show that: School promotion marketing strategies in increasing the competitiveness of institutions are using print media strategies, online media, Word of Moths, and direct promotion every day by providing new innovations such as social activities to the surrounding community. The marketing strategy of school products in increasing the competitiveness of institutions is to bring up many new innovations by creating pesantren-style education, namely with excellent programs such as tahfidz class programs, selected hadith memorization programs, Quran takhosus memorization programs, Quran certification programs, dhuha prayer programs, congregational dhuhur prayer programs. Likewise, school programs where early subjects dominate than general subjects, namely 65% of early subjects. And coupled with the tahfidz program at Al-Unaizy elementary school, it is an attraction to increase the school's PPDB titative. In addition, it also improves the quality of teachers and the quality of adequate facilities and infrastructure.